Consumption of beef sandwiches in the United States and contributions to intake of energy and select nutrients - Murphy, Mary M.; Anderson, Maribeth M.; Bi, Xiaoyu (Frontiers in Nutrition, 2024)
Introduction: Sandwiches are commonly consumed in the United States. This study summarizes contributions of beef sandwiches to energy and select nutrient intakes.Methods: Beef sandwiches were categorized as beef burger sandwiches (hamburgers or cheeseburgers) and non-burger beef sandwiches. Per capita and per user intakes of beef sandwiches (total and by type) and contributions to total nutrient intakes from beef and non-beef sandwich components were estimated for the population ages ≥2 years (n=15,984) participating in WWEIA/NHANES, 2013-2016.Results: On any given day, 21.4% of the population consumed a beef sandwich. Among all Americans, beef sandwiches provided 6.3% of mean energy intake and accounted for approximately 10% of the population's mean intake of vitamin B12 and saturated fat, 9% of protein and sodium, 7% of iron, 6% of choline, and 5% of potassium. Among beef sandwich consumers, beef sandwiches accounted for 26.3% of mean energy intake on a day of consumption. The beef component of sandwiches accounted for the majority of vitamin B12, choline, and protein, non-beef components accounted for the majority of sodium, iron, and potassium, and beef and non-beef components made similar contributions to saturated fat.Hamburgers provided consumers the lowest energy, sodium, and saturated fat intake, while nonburger sandwiches provided the highest intake of these nutrients.Discussion: Beef sandwiches are an important source of energy, protein, vitamin B12, iron, and choline, and like other sandwiches, are also a source of sodium and saturated fat. Americans could enhance nutrient contributions from sandwiches by selecting lean meat and limiting use of saturated fat-or sodium-rich components.